Risks in Antibiotic Substitution Following Medicine Shortage: A Health-Care Failure Mode and Effect Analysis of Six European Hospitals - Miljković, Nenad; Godman, Brian; van Overbeeke, Eline; Kovačević, Milena; Tsiakitzis, Karyofyllis; Apatsidou, Athina; Nikopoulou, Anna; Yubero, Cristina Garcia; Portillo Horcajada, Laura; Stemer, Gunar; Kuruc-Poje, Darija; De Rijdt, Thomas; et al. (Frontiers in Medicine, 2020)
Introduction: Medicine shortages result in great risk for the continuity of patient care especially for antimicrobial treatment, potentially enhancing resistance rates and having a higher economic impact. This study aims to identify, describe, assess, and assign risk priority levels to potential failures following substitution of antimicrobial treatment due to shortages among European hospitals. Furthermore, the study investigated the impact of corrective actions on risk reduction so as to provide guidance and improve future patient care. Methods: Health-care failure mode and effect analysis (HFMEA) was applied to hospitals in Austria (H-AT), Belgium (H-BE), Croatia (H-CR), Greece (H-GR), Spain (H-SP), and Serbia (H-SR). Multidisciplinary teams identified processes, failure modes, causes, and corrective actions related to antibiotic substitution following medicine shortages. Characteristics of study hospitals as well as severity, probability, and hazard scores (HSs) of failure modes/causes were analyzed using Microsoft Office Excel 2010 and IBM SPSS Statistics® via descriptive and inferential statistics. Results: Through HFMEA, 74 failure modes were identified, with 53 of these scoring 8 or above on the basis of assigned severity and probability for a failure. Severity of failure modes differed before and after corrective actions in H-CR, H-GR, and H-SR (p < 0.005). Their probability differed in all study hospitals (p < 0.005) when compared before and after corrective actions aimed to be implemented. The highest number of failure-mode causes was detected in H-CR (46) and the lowest in H-SP (16). Corrective actions can address failure modes and lower HSs; therein, all teams proposed the following: structuring communication among stakeholders, introducing electronic prescribing, strengthening pharmacists' involvement, and increasing effectiveness of the ward stock assessment. These proposed actions led to HS reductions up to 83%. Conclusion: There is a lack of structure in addressing risks associated with antibiotic substitution following shortages. Furthermore, lack of communication, data scarcity on availability of antibiotics, non-supportive information technology (IT) systems, and lack of internal substitution protocols hinder quick assessment of alternatives addressing patient needs. Nevertheless, the study shows that health-care professionals manage to secure optimal antimicrobial treatment for patients using available IT and human resources.